Generation Y’s Leadership Preferences and Their Influence on Work Performance - Jiri KOLENAK; David ULLRICH; Veronika KOLENAKOVA; Daria SEVCIKOVA (Communications of International Proceedings, 2020)
The objective of this article is to analyze the generation Y’s leadership types preferences. We build upon the presumption that identifying preferences and the effort of satisfying them for a given group of workers, will lead to the enhancement of their work performance. We presume that, apart from higher performance, there will also be a lessening of its fluctuation as well as enhancement of the quality of life perception. The theory section of the article deals with the characteristics of individual generations and with major leadership theories. Research section examines the preferences of the generation Y members in the area of leadership and the subjective rating of the current state of affair in that area. The modified Full Range Leadership Model was chosen as a suitable tool for the analysis. The results of the analysis show that the preferred leadership style is the interviewed sample of respondents from generation Y is transformational leadership. 30% of respondents are dissatisfied with the current leadership style in the company, and the share of satisfaction with their direct superior is higher. The results showed that the way Generation Y is conducted at work is crucial to it; 96% of respondents said that management has a direct influence on their successful retention.
Keywords: Leadership styles; work performance; generation Y; MLQ